IMPLEMENTASI SAK EMKM DAN KEPATUHAN WAJIB PAJAK PELAKU UMKM DI KOTA MATARAM - Setiawati, Elvina (Universitas Sam Ratulangi, 2021)
This study aims to examine and analyze the effect of understanding the financial accounting standard for MSMEs (or SAK EMKM) and readiness for implementing it on taxpayer compliance. The data are collected through questionnaires on MSMEs in the Mataram City and analyzed by multiple linear regression. The results show that the understanding of SAK EMKM has a positive and significant effect on taxpayer compliance but the readiness to implement SAK EMKM is insignificant on taxpayer compliance. Basically, MSMEs in Mataram City are quite familiar with SAK EMKM, but due to the lack of human resources in the accounting sector, the implementation of SAK EMKM has not been fully implemented. This of course will give difficulties to the MSMEs in the Mataram City in preparing financial reports so that it will affect the accurate and correct tax calculation. In other words, the tax report is not submitted on time.